Protic organic ionic plastic crystals based on a difunctional cation and the triflate anion: a new solid-state proton conductor. Issue 98 (7th November 2016) - Rao, Jun; Vijayaraghavan, R.; Chen, Fangfang; Zhu, Haijin; Howlett, Patrick C.; MacFarlane, Douglas R.; Forsyth, Maria
Abstract : A new family of ammonium based organic ionic plastic crystals exhibits exciting solid-state proton conductivity. Abstract : Two protic organic ionic plastic crystalline materials based on the mono- and di-protonated cations of N, N -dimethylethylenediamine, (DMEDA) and the triflate anion have been studied. The symmetrical di-protonated cation salt shows 54 °C higher melting point and 24-fold higher conductivity at room temperature as compared to the mono-protonated cation salt, making it a promising candidate for a solid-state proton conductor. The conductivity of this salt was further enhanced by acid doping.